Regulation of Halal and Healthy Products for Small-scaled Businesses as Consumer Protection - Hasanah, Neneng Uswatun; Safira, Martha Eri; Kurnianingtyas Sri Agung, Winantu; Chotib, Mochammad; Nimasari, Elok Putri; Lahuri, Setiawan Bin (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The purpose of the study was to know the regulation on halal and health guarantee of Indonesian snacks such as cilok (tapioca balls), grilled meatballs, meatball and chicken noodles, dawet drink (traditional drink from rice flour and coconut milk), crackers, and grass jelly drink. Such snacks and drinks are loved by all levels of society in Indonesia and are often sold by street vendors in various places. METHOD: This research uses a juridical-sociological approach, by analyzing the primary source of data, which is by directly observing, interviewing, and educating the society and the small-scale sellers on the important sense of the halal product and the halal product certification. Apart from that, the primary data are the Law No. 8 of 1999 on the Consumer Protection, the Law No. 33 of 2014 on the Halal Product Guarantee, and the Governmental Decree No. 31 of 2019 on the Halal Product Certification. RESULTS: The realization of consumer protection requires good coordination between the government and/or regional governments, business actors, and the community as consumers. The need for halal and healthy products is not only for Muslim communities but also for non-Muslim communities, because halal products are certainly guaranteed of the products’ hygiene and safety. CONCLUSION: There is still a lack of understanding and compliance by the small business owners on the halal and healthy products from the manufacturing process up to the distribution of the products to the public.